Penggunaan Video untuk Memperkaya Share Informasi Pembelajaran Fisika pada Model Two Stay Two Stray: The Use of Video to Enhance Shared Information of Physics Teaching using Two Stay Two Stray Model - Munawaroh Munawaroh; Upik Yelianti; Damris Muhammad (Universitas Jambi, 2020)
Model of teaching Two Stay Two Stray (TSTS) requires group of students to share information back to their own group from their counterpart groups. The shared information is limited as oral information dominantly shared during the teaching processes. The objective of this study was to improve shared information between groups of students in physics learning by using video at Madrasah Aliyah Nurul Jalal Tebo. The video was played to enhance shared information between groups of students using TSTSlearning model. Video was shown to the incoming students to enhance oral explanation. The number of information shared between these groups of students was compared with conventional TSTS class. Two-way anova was used to analyze the data. The results show that the use of video in TSTS learning is not significantly affect the shared information between groups of students.